Perioperative nutritional support. Guidelines of the All-Russian public organization “Federation of Anesthesiologists and Reanimatologists” - I.N. Leyderman; A.L. Potapov; I.N. Pasechnik; I.B. Zabolotskikh; E.A. Kokarev; K.M. Lebedinskii; Yu.P. Orlov; M.V. Petrova; A.A. Ryk; S.V. Sviridov; E.Yu. Strukov; A.V. Sytov; et al. (Russian Journal of Anesthesiology and Reanimatology, 2026)
The development of protein-energy malnutrition (PEM) syndrome is a pressing issue in surgical settings. The risk of malnutrition developing is determined in the majority of patients admitted to surgical wards. 30–70% of patients demonstrate signs of PEM upon admission, and during treatment, this syndrome can progress, reaching 50–60%. The severity of PEM is closely connected with clinical outcome indicators: length of stay in the intensive care unit and hospital increases, infectious complications occur more frequently, and treatment costs increase significantly. These guidelines, based on the principles of evidence-based medicine, describe methods for diagnosing and correction of PEM at all stages of surgical treatment. Also practical algorithms and criteria for evaluation the quality of nutritional and metabolic support during the perioperative period are included in this paper.